Culturally Conscientious Pain Measurement in Older African Americans. (October 2016) - Booker, Staja Q.; Herr, Keela A.; Tripp-Reimer, Toni
Despite considerable pain disparities across the care continuum, pain is an understudied health problem in older ethnic minority groups, such as African Americans. Quality pain measurement is a core task in pain management and a mechanism by which pain disparities may be reduced. Pain measurement includes the methods (e.g., assessment approaches, tools) and metrics that researchers and clinicians use to understand the characteristics of pain. However, there are significant issues and gaps that negatively affect pain measurement in older African Americans. Of concern is insufficient representation in pain research, which impedes the testing and refinement of many standardized self-report, behavioral and surrogate report, physiological, and composite measures of pain. The purposes for this article are to discuss the status of pain measurement and factors that affect our knowledge on pain measurement in older African Americans, and to provide guidance for culturally conscientious pain measurement using the available literature.